2019
DOI: 10.1186/s12886-019-1245-4
|View full text |Cite
|
Sign up to set email alerts
|

Five-year real-world outcomes of anti-vascular endothelial growth factor monotherapy versus combination therapy for polypoidal choroidal vasculopathy in a Chinese population: a retrospective study

Abstract: BackgroundTo evaluate 5-year outcomes of anti-vascular endothelial growth factor (VEGF) monotherapy and combination therapy of anti-VEGF agents and photodynamic therapy (PDT) for polypoidal choroidal vasculopathy (PCV) in a real-world Chinese population.MethodsRetrospective study. Fifty-three eyes of 46 patients with subtype 1 and 2 PCV followed up for at least 60 months were grouped into three regimens: anti-VEGF monotherapy, PDT combining with anti-VEGF therapy initially, and PDT combining with deferred anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several studies reported long-term results of the combination therapy involving PDT and anti-VEGF agents for PCV. [13,16,17] Miyata et al reported 5-year results after combination therapy involving PDT and intravitreal injection of ranibizumab for 20 eyes with PCV. In their report, BCVA significantly improved at 1 year, but thereafter BCVA declined and returned to baseline value at 5 year.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported long-term results of the combination therapy involving PDT and anti-VEGF agents for PCV. [13,16,17] Miyata et al reported 5-year results after combination therapy involving PDT and intravitreal injection of ranibizumab for 20 eyes with PCV. In their report, BCVA significantly improved at 1 year, but thereafter BCVA declined and returned to baseline value at 5 year.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of feeder vessels per se defined that the subject had type 1 PCV; therefore, our findings indicated differences in outcome between type 1 PCV and type 2 PCV, in agreement with existing reports. 28 , 29 However, the use of margins ≥500 μm tended to yield better outcomes than using margins <500 μm. Moreover, a similar tendency was observed for classic lesions and occult lesions on FA.…”
Section: Discussionmentioning
confidence: 98%
“…The relevance of our study on systemic risk factors for VH in patients with PCV lies in the suggestion that patients with PCV with high WBC and impaired coagulation function should pay more attention to the probability of VH. With the help of our nomogram, high-risk patients with PCV should actively cooperate with ophthalmologists in adhering to a treatment plan before the occurrence of VH, such as prompt anti-vascular endothelial growth factor (VEGF) therapy or combined therapy, with the aim to effectively limit the progression of PCV [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%